2020
DOI: 10.3390/polym13010070
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Silicate-Activated Gelatin Methacrylate Hydrogel for Accelerating Human Dermal Fibroblast Proliferation and Differentiation

Abstract: Wound healing is a complex process that requires specific interactions between multiple cells such as fibroblasts, mesenchymal, endothelial, and neural stem cells. Recent studies have shown that calcium silicate (CS)-based biomaterials can enhance the secretion of growth factors from fibroblasts, which further increased wound healing and skin regeneration. In addition, gelatin methacrylate (GelMa) is a compatible biomaterial that is commonly used in tissue engineering. However, it has low mechanical properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…As shown, increasing the concentrations of Si positively regulated the stress, with Si0.5 and Si1.0 increasing the stress by 30% and 69% than Si0, respectively. As reported previously, the addition of Si ions increased Si-OH bonds, thus increasing the overall mechanical properties of the hydrogels [20]. According to the rheological and mechanical test, Yu et al demonstrated that the addition of CS material could significantly regulate the printability compared to FGelMa alone, and with the increased concentration of CS material, the mechanical properties increased [36].…”
Section: Synthesis and Characterization Of The Fgelma And Alg/gel Hydrogelsmentioning
confidence: 66%
See 1 more Smart Citation
“…As shown, increasing the concentrations of Si positively regulated the stress, with Si0.5 and Si1.0 increasing the stress by 30% and 69% than Si0, respectively. As reported previously, the addition of Si ions increased Si-OH bonds, thus increasing the overall mechanical properties of the hydrogels [20]. According to the rheological and mechanical test, Yu et al demonstrated that the addition of CS material could significantly regulate the printability compared to FGelMa alone, and with the increased concentration of CS material, the mechanical properties increased [36].…”
Section: Synthesis and Characterization Of The Fgelma And Alg/gel Hydrogelsmentioning
confidence: 66%
“…Various types of techniques have been developed to promote angiogenesis for tissue engineering such as controlling pore sizes, pore stiffness, surface topography, modification of biomaterials, and inclusion of endothelial cells or growth factors. Our previous results showed that inclusion of calcium silicate (CS) products into GelMa were able to enhance angiogenesis via increasing the secretion of VEGF from fibroblasts [20]. In fact, CS is the bioceramic that is always used as an endodontics material for root repair [21].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we successfully fabricated Si-infused GelMa hydrogels. The results showed that these Si-infused GelMa hydrogels were superior to pure GelMa hydrogels in both in vitro and in vivo studies [15]. However, to the best of our knowledge, there are currently no studies reporting on GelMa in combination with CS powder for use in odontogenesis.…”
Section: Introductionmentioning
confidence: 91%
“…An ideal scaffold should be non-toxic, yet bioactive, and most importantly, it should be able to provide a 3D microenvironment similar to native tissues that supports cell growth, proliferation, and differentiation [12][13][14]. In recent years, several studies demonstrated that the microenvironment of a 3D hydrogel is closer to the real situation than the 2D culture method because it can improve the proliferation and differentiation functions during the cell culture process [15]. Prescott et al fabricated a hDPSCs-encapsulated collagen I hydrogel with a growth factor dentin matrix protein-1 (DMP-1) that induced formation of dental pulplike tissues from hDPSCs [16].…”
Section: Introductionmentioning
confidence: 99%
“…Extracellular matrix (ECM) plays a key role in the successful regeneration of the nerve tissue 1–3 to provide a suitable environment for cell attachment, growth, and proliferation of cells 4 . The electrospinning method is one of the most effective ways to mimic the native ECM by means of the preparation of nanofibrous scaffolds 5–7 due to interconnected porous morphology, 8 modulated fiber diameter and pore size and the ultrahigh surface to volume ratio.…”
Section: Introductionmentioning
confidence: 99%